Report from the international agriculture research centres of the consultative group on international agricultural research to the intergovernmental technical working group on plant genetic resources for food and agriculture - Food and Agriculture Organization of the United Nations (Food and Agriculture Organization of the United Nations, 2011)
This document presents a report on the activities undertaken by the Centres of the Consultative Group on International Agricultural Research (CGIAR)1 in relation to genetic resources for food and agriculture (GRFA).